Esophagogastrostomy With Fundoplication Versus Double-tract Reconstruction After Laparoscopic Proximal Gastrectomy for Gastric Cancer. Issue 5 (October 2021) - Tominaga, Shinta; Ojima, Toshiyasu; Nakamura, Masaki; Katsuda, Masahiro; Hayata, Keiji; Kitadani, Junya; Takeuchi, Akihiro; Motobayashi, Hideki; Nakai, Tomoki; Yamaue, Hiroki
Abstract : Purpose: We investigated that double-tract reconstruction (DTR) may be more beneficial than esophagogastrostomy (EG) with fundoplication in terms of nutritional outcomes, focusing on loss of body weight. Materials and Methods: This study included 56 consecutive patients with early gastric cancer in the upper third of the stomach who received laparoscopic proximal gastrectomy, 39 underwent EG. In the 17 patients requiring resection of the abdominal esophagus or where the size of the remnant stomach was 50% or less, we performed DTR. Results: There was no significant difference in the rate of body weight change at 6 or 12 months, or in biochemical markers (hemoglobin, total protein, and albumin) at 12 months. However, 8 patients in the EG group had extreme body weight loss (≥20%) within 12 months. Conversely, in the DTR group, no patients had any extreme body weight loss. Conclusion: DTR is useful after laparoscopic proximal gastrectomy, especially in terms of preventing extreme body weight loss. Abstract : Supplemental Digital Content is available in the text.